Mucin Expression in Endoscopic Ultrasound-Guided Fine-Needle Aspiration Specimens Is a Useful Prognostic Factor in Pancreatic Ductal Adenocarcinoma. Issue 5 (July 2015) - Higashi, Michiyo; Yokoyama, Seiya; Yamamoto, Takafumi; Goto, Yuko; Kitazono, Ikumi; Hiraki, Tsubasa; Taguchi, Hiroki; Hashimoto, Shinichi; Fukukura, Yoshihiko; Koriyama, Chihaya; Mataki, Yuko; Maemura, Kosei; et al.
Abstract : Objectives: The aim of this study was to further examine the utility of mucin (MUC) expression profiles as prognostic factors in pancreatic ductal adenocarcinoma (PDAC). Methods: Mucin expression was examined by immunohistochemistry analysis in endoscopic ultrasound-guided fine-needle aspiration specimens obtained from 114 patients with PDAC. The rate of expression of each MUC was compared with clinicopathologic features. Results: The expression rates of MUCs in cancer lesions were MUC1, 87.7%; MUC2, 0.8%; MUC4, 93.0%; MUC5AC, 78.9%; MUC6, 24.6%; and MUC16, 67.5%. MUC1 and MUC4 were positive, and MUC2 was negative in most PDACs. Patients with advanced stage of PDAC with MUC5AC expression had a significantly better outcome than those who were MUC5AC-negative ( P = 0.002). With increasing clinical stage, total MUC6 expression decreased ( P for trend = 0.001) and MUC16 cytoplasmic expression increased ( P for trend = 0.02). The prognosis of patients with MUC16 cytoplasmic expression was significantly poorer than those without this expression. Multivariate survival analysis revealed that MUC16 cytoplasmic expression was a significant independent predictor of a poor prognosis after adjusting for the effects of other prognostic factors ( P = 0.002). Conclusions: Mucin expression profiles in ultrasound-guided fine-needle aspiration specimens have excellent diagnostic utility and are useful predictors of outcome in patients with PDAC.